2012
DOI: 10.1080/00087114.2012.760878
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphology of Brassica napus × B. rapa hybrids and patterns of variation in the F2 derivatives

Abstract: The present study was carried out to determine crossability between Brassica napus and B. rapa, to elucidate chromosome homoeology between different Brassica genomes in the F 1 hybrids and to estimate genetic variability in F 2 progenies of the crosses. Crosses between B. napus (AACC, 2n = 38) and B. rapa (AA, 2n = 20) vars. brown sarson, yellow sarson and toria were attempted and the hybrid derivatives were advanced to F 2 generation. Hybrid recoveries were higher when B. napus was used as a female parent. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Orientation of the chromosomes at metaphase I and disjunction of chromosome at anaphase I and II was found abnormal (Meng et al, 1998;Souza, 1999;Gupta et al, 2014). In addition to these bridge-fragment con guration was also observed at anaphase I and anaphase II (Choudhary et al, 2012). As per the observations B. carinata performed better as a seed parent with B. nigra, B. juncea and B. rapa whereas, with B. napus it performed good as a pollen parent.…”
Section: Discussionsupporting
confidence: 73%
“…Orientation of the chromosomes at metaphase I and disjunction of chromosome at anaphase I and II was found abnormal (Meng et al, 1998;Souza, 1999;Gupta et al, 2014). In addition to these bridge-fragment con guration was also observed at anaphase I and anaphase II (Choudhary et al, 2012). As per the observations B. carinata performed better as a seed parent with B. nigra, B. juncea and B. rapa whereas, with B. napus it performed good as a pollen parent.…”
Section: Discussionsupporting
confidence: 73%
“…Reciprocal crosses were generally unsuccessful. Moreover, Choudhary et al (2012) demonstrated that amongst crosses involving three varieties/forms of B. rapa with B. napus, yellow sarson produced a maximum number of hybrids (18.0%) followed by brown sarson (11.3%) and toria (6.9%). Thus, the success rate of cross-fertility of three varieties of B. rapa with B. napus was in the order yellow sarson > brown sarson > toria.…”
Section: Discussionmentioning
confidence: 99%
“…To date, successful attempts of hybridization between Brassica rapa and Brassica napus have been published in numerous scientific papers (Fitz et al, 2007;Choudhary et al, 2012). Crossability between B. napus and B. rapa has also been examined, specifically in terms of the genes introgression from B. napus to B. rapa , which is mainly considered a weed in America and Europe (Tsuda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%